2008
DOI: 10.1074/mcp.m800100-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomics Study Reveals That Bacterial CpG Motifs Induce Tumor Cell Autophagy in Vitro and in Vivo

Abstract: In addition, we observed an increased glyceraldehyde-3-phosphate dehydrogenase expression, which has been shown to be sufficient to trigger an autophagic process. Autophagy is a self-digestion pathway whereby cytoplasmic material is sequestered by a structure termed the autophagosome for subsequent degradation and recycling. As bacteria are known to trigger autophagy, we assessed whether bacterial CpG motifs might induce autophagy in TLR9-positive tumor cells. We showed that CpG-ODN can induce autophagy in rod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…Recent studies suggest that TLRs, the primary cellular sensors for PAMPs, can regulate autophagy through the stimulation of downstream signaling pathways in macrophages and other cells types (19). For example TLR9 ligands (i.e., bacterial CpG motifs), can induce autophagy in rodent and human tumor cell lines (2). Furthermore, the TLR7 ligands, single-stranded RNA (ssRNA) and imiquimod were found to be potent inducers of autophagy (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that TLRs, the primary cellular sensors for PAMPs, can regulate autophagy through the stimulation of downstream signaling pathways in macrophages and other cells types (19). For example TLR9 ligands (i.e., bacterial CpG motifs), can induce autophagy in rodent and human tumor cell lines (2). Furthermore, the TLR7 ligands, single-stranded RNA (ssRNA) and imiquimod were found to be potent inducers of autophagy (6).…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 specifically recognizes the LPS of gram-negative bacteria (13). Recently, several TLRs, including TLR4, have been identified as also exerting a role in the regulation of autophagy (2,6,9,17,19,28,32). TLR4 has a role of maintaining constitutive lung integrity by modulating oxidant generation.…”
mentioning
confidence: 99%
“…87 In support of this, GAPDH upregulation induced by bacterial CpG motifs in colon carcinoma cells was correlated with an increase in autophagy in vitro and in vivo. 93 The elevated ATP levels as a result of glycolysis, and the function of autophagy to remove damaged mitochondria, both coordinated by GAPDH, cooperate in this protection toward CICD (Figure 3). However, in this study, protection from CICD involved GAPDH overexpression; therefore, further studies are required to unravel the mechanism whereby GAPDH protects cells from CICD under physiological conditions.…”
Section: Gapdh As a Prosurvival Factormentioning
confidence: 99%
“…Indeed, we showed that CpG-ODN can induce autophagy in tumor cell lines from colon, breast and prostate cancers and that TLR9 was required for this process. 15 In addition, an increase in the number of autophagosomes can also be observed in vivo after intratumoral injection of CpG-ODN or plasmid-based CpG motifs in a rat model of liver metastasis.…”
Section: Tlr Ligands and Autophagymentioning
confidence: 92%
“…22,23 It is proposed that TLR9 localized in the ER gains access to incoming endosomes were cultured in the presence of CpG or control-ODN at a final concentration of 10 µg/mL for 40 h and processed for transmission electron microscopy as described previously. 15 Mitochondria presenting normal morphology can be observed in control-ODN-treated cells, whereas swollen mitochondria engulfed within large autophagosomes are noted in CpG-ODN-treated cells. The arrow points to an autophagosome containing damaged mitochondria.…”
Section: Role Of Autophagy In Tlr9 Relocalizationmentioning
confidence: 96%